Analysis of Differentiation Strategies to Create Competitive Advantages in Facing Global Markets - Putra, Y S; ., Sudarmiatin; ., Suharto (KnE Social Sciences, 2018)
Facing the era of global competition, every company is required to be able to have a competitive advantage in business both in terms of goods and service. Similarly, with the brand Never Get Old Company jeans. This study aims to analyze the differentiation strategy in the business of Never Get Old Company brand convection in Malang city in creating competitive advantage. This research uses descriptive qualitative approach. Data collection techniques used are observation, interview, and documentation. The location of the study was on Uranium road no. 66 Purwantoro, Blimbing, Malang, which is a place of production as well as where to sell jeans products. Subjects of research are owners, employees, customers and business partners. This research uses descriptive qualitative design with triangulation of data source and method. Data analysis using SWOT is preceded by IFAS and EFAS analysis. The research findings indicate that the differentiation strategy performed on brand convention business Never Get Old Company is product differentiation, service differentiation, and brand differentiation. Differentiation is an important factor for the success of a business in achieving competitive advantage. Based on the value of IFAS and EFAS, SWOT diagrams are generated in quadrant 1 that supports aggressive strategies. While the result of SWOT matrix, an alternative strategy that can be used is SO strategy. This suggests that differentiation strategies can create competitive advantage in the Never Get Old Company brand denim business in the face of global markets. The recommendation of this research is that the business owner should provide an outlet to install product displays and create an official website on the Never Get Old Company brand convection business. Keywords: SWOT Analysis, Differentiation, Competitive Advantage